2021
DOI: 10.1590/0100-5405/241384
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de Bacillus spp. em promover o crescimento e controlar Fusarium verticillioides em milho

Abstract: RESUMO O tratamento de sementes com microrganismos visando promoção de crescimento e controle de Fusarium verticillioides é uma tecnologia que poderá ser utilizada para ampliar a sustentabilidade da cultura do milho. Para tanto, estudos com a utilização de microrganismos para tratamento de sementes visando ao controle de F. verticillioides e promoção de crescimento vegetal em milho são necessários para o desenvolvimento de bioprodutos. Onze isolados de Bacillus spp. foram testados quanto às características bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In the absence of inoculation, PSS survival of 82.4% corroborates with the results found by Almeida Neto et al [67]. Although no other studies evaluate PSS survival in the field under the use of microorganisms, studies reported the PGPB action in improving rooting and nutritional aspects [37,[68][69][70][71].…”
Section: Discussionsupporting
confidence: 86%
“…In the absence of inoculation, PSS survival of 82.4% corroborates with the results found by Almeida Neto et al [67]. Although no other studies evaluate PSS survival in the field under the use of microorganisms, studies reported the PGPB action in improving rooting and nutritional aspects [37,[68][69][70][71].…”
Section: Discussionsupporting
confidence: 86%
“…Regardless of the B. amyloliquefaciens dose used, Fusarium failed to show differentiation for the control of rot, persisting in all doses in the evaluated grains (Table 3), disagreeing with that observed by Ferreira et al (2021), which affirms that the use of Bacillus spp. is promising for the corn crop in Fusarium control.…”
Section: Resultsmentioning
confidence: 73%